2004
DOI: 10.1002/chin.200451103
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxy‐6‐methyl‐3‐(5‐phenyl‐2E,4E‐pentadien‐1‐oyl)‐2H‐pyran‐2‐one: Synthesis and Reactivity with Amines.

Abstract: The synthesis and reactivity studies of 4-hydroxy-6-methyl-3-(5-phenyl-2E, 4E-p e n t a d i e n -1 -o y l ) -2H-p y r a n -2-one 2 with nucleophiles are reported. Reactions of 2 with hydrazine derivatives gave new pyrazole-type compounds while the reaction with o rt h o-phenylenediamines yielded 1,5-benzodiazepines. The reaction of 2 w i t h ethylamine implies the 2H-pyran-2-one ring opening and the formation of a strong conjugated compound 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The structure of the obtained products 9-11 was determined by reference to the ring substituents and are a consequence of the starting 1,2-phenylenediamines 7b-d. When an electron-donating group is present (CH 3 , Cl), the 1-NH 2 reacts first, whereas for an electron-withdrawing substituent (NO 2 ), the 2-NH 2 group reacts first, giving products 9-11 after a cyclocondensation reaction [24][25][26]. The 13 C NMR spectrum of 9 confirms a 4-hydroxy-2-pyrone ring whereas in compounds 10 and 11, the presence of the methine group of a b-ketoester system is amply confirmed using HSQC and HMBC correlations (H-3!C-3 and C-2 0 ; H-3 0 !C-3 and C-10; NH!C-5 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the obtained products 9-11 was determined by reference to the ring substituents and are a consequence of the starting 1,2-phenylenediamines 7b-d. When an electron-donating group is present (CH 3 , Cl), the 1-NH 2 reacts first, whereas for an electron-withdrawing substituent (NO 2 ), the 2-NH 2 group reacts first, giving products 9-11 after a cyclocondensation reaction [24][25][26]. The 13 C NMR spectrum of 9 confirms a 4-hydroxy-2-pyrone ring whereas in compounds 10 and 11, the presence of the methine group of a b-ketoester system is amply confirmed using HSQC and HMBC correlations (H-3!C-3 and C-2 0 ; H-3 0 !C-3 and C-10; NH!C-5 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dehydroacetic acid has been reported to generate a number of heterocyclic compounds through ring opening and recyclization upon treatment with a variety of binucleophiles [37][38][39][40][41]. In 1991 Bendaas et al reported the synthesis of 4-acylacetyl-5-hydroxy-1-phenylpyrazoles (I) [42] (Scheme 3).…”
Section: Chemistrymentioning
confidence: 99%